Health Care Workers Practices That Influence Adherence to National HIV and AIDS Guidelines for Adults at Chuka and Chogoria Hospital - Micheni, Purity Gakii; Gitonga, Professor Lucy; Kiongo, Dr. Josphat; Micheni, Hellen N. (American Journal of Health, Medicine and Nursing Practice, 2025)
Purpose: Adherence by the health workers to the Kenya National HIV and AIDS Management Guidelines on the prevention and treatment aims at minimizing new infections, increasing effectiveness of HIV and AIDS treatment and reducing the cost incurred by the government in the purchase of the drugs. The general objective of this study was to establish health care workers practices that influence adherence to national HIV and AIDS guidelines for adults at chuka and Chogoria hospital. Materials and Methods: The hospitals were selected because they have the highest HIV and AIDS patients with a workload of 1,406 and 2,704 for Chuka and Chogoria Hospital, respectively. A cross-sectional descriptive study design was adopted. The study targeted the following strata: nurses, clinical officers, nutritionists, pharmaceutical technicians, laboratory technicians, medical officers and HIV testing service personnel at Chuka Hospital and Chogoria Hospital. This study therefore computed 20% of each stratum in both hospitals resulting to 71 respondents who were selected randomly. The information was gathered utilizing a standardized questionnaire that had been pre-tested at the Marimanti Hospital. The study obtained reliability coefficients of above 0.90 for all variables indicating that the instrument was reliable. Data was analyzed using SPSS version 25.0 for windows. For data analysis, frequencies, percentages, mean, and standard deviation were used, and the results were displayed in tables and pie charts. Findings: The results showed that 100% of health workers regarded the national guidelines for management of HIV and AIDS as effective. However, adherence at Chogoria Hospital was only 25.8% compared to Chuka Hospital which was at 63.6%. From the study, only 34.8% of the healthcare workers had read the National guidelines for management of HIV and AIDS, while 65.2% had not. However, Chogoria Hospital had more health workers that had read (45.5%) than those in Chuka Hospital (29.5%). Unique Contribution to Theory, Practice and Policy: The study recommends that hospitals, policy makers, medical educators and health care managers need to provide training and support so as to increase health workers knowledge, awareness, familiarity and compliance with the guidelines.